2013
DOI: 10.1038/mp.2013.66
|View full text |Cite|
|
Sign up to set email alerts
|

Reelin, an extracellular matrix protein linked to early onset psychiatric diseases, drives postnatal development of the prefrontal cortex via GluN2B-NMDARs and the mTOR pathway

Abstract: Defective brain extracellular matrix (ECM) is a factor of vulnerability in various psychiatric diseases such as schizophrenia, depression and autism. The glycoprotein reelin is an essential building block of the brain ECM that modulates neuronal development and participates to the functions of adult central synapses. The reelin gene (RELN) is a strong candidate in psychiatric diseases of early onset, but its synaptic and behavioral functions in juvenile brain circuits remain unresolved. Here, we found that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 65 publications
6
124
0
Order By: Relevance
“…We observed a mean of ∌40 seizures in col19a1 −/− mutants over 5 d (37.7 ± 5.4 [mean ± SEM] seizure-like events, n = 9, versus 5.8 ± 4.8 in controls, n = 6). Although this number seems high, it is comparable to other mouse models of schizophrenia (e.g., 51.5 ± 2.5 seizure events in reln rl/+ heterozygotes, n = 2; Iafrati et al, 2014).…”
Section: Loss Of Collagen XIX Leads To Schizophreniarelated Behaviorssupporting
confidence: 76%
See 1 more Smart Citation
“…We observed a mean of ∌40 seizures in col19a1 −/− mutants over 5 d (37.7 ± 5.4 [mean ± SEM] seizure-like events, n = 9, versus 5.8 ± 4.8 in controls, n = 6). Although this number seems high, it is comparable to other mouse models of schizophrenia (e.g., 51.5 ± 2.5 seizure events in reln rl/+ heterozygotes, n = 2; Iafrati et al, 2014).…”
Section: Loss Of Collagen XIX Leads To Schizophreniarelated Behaviorssupporting
confidence: 76%
“…Mice with a spontaneous mutation in the reln gene (reln rl/rl ; also called reeler mutant mice) were identified more than 60 years ago (Falconer, 1951). Recent studies have demonstrated that mice lacking a single copy of reln (reln rl/+ ) display traits associated with complex brain disorders (Iafrati et al, 2014).…”
Section: Animalsmentioning
confidence: 99%
“…We previously reported that reduced Reelin signaling in juvenile heterozygous reeler or Dab1 KO mice leads to a reduction in dendritic spine density in the hippocampus (Niu et al, 2008). Recent findings further demonstrated that spinogenesis and long-term synaptic plasticity are impaired in the prefrontal cortex of juvenile heterozygous reeler mice (Iafrati et al, 2013). Based on these findings, we predict that there is a postnatal window during which Reelin signaling promotes spinogenesis.…”
Section: Discussionmentioning
confidence: 55%
“…Spontaneous mutant mice lacking Reelin (reeler) or Dab1 (scrambler), and Dab1 knock-out (KO) mice present with widespread defects in cellular layer formation Howell et al, 1997Howell et al, , 2000Sheldon et al, 1997). A developmental delay in dendrite and axon branching, as well as spine formation and synaptogenesis, has been also reported in the hippocampus of Reelin and Dab1 mutant mice Niu et al, 2004Niu et al, , 2008Borrell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation